Can customer loyalty created by online brand experience affect physical product sales? - Jin, Yuchen (2022)
The brand experience has been a focus of research in the marketing field since it was introduced. Numerous studies have previously demonstrated that brand experience has a positive impact on customer loyalty. In addition, brand experience has also been shown to be a multi-dimensional construct, with each dimension having a different degree of impact on customer loyalty. Nowadays, with the popularity of the internet, it is becoming more and more common to offer brand experiences to customers in an online environment. In this new era, a category of virtual brands has emerged that offer customers an online brand experience solely through their app or website. Previous research on brand experience and customer loyalty has mainly focused on offline brand experiences. This study pays attention to the online health brands in China, with the aim of examining whether virtual brands can still have a positive impact on customer loyalty despite the online only brand experience they provide. Furthermore, once some online health brands have gained a stable user base through their apps or websites, they have begun to expand their marketing and develop related offline products through brand extension. Previous research has demonstrated that both brand experience and customer loyalty have a positive effect on brand extension. However, as the virtual brands are a type of brand that has emerged since the popularity of the internet, there is little research on the development of offline extensions for virtual brands. The second objective of this study is to fill this research gap by examining whether customer loyalty, influenced by the online brand experience, has a positive effect on the sale of these products when these online brands extend their brands offline to launch physical products.